The Neuronal Circuit of the Dorsal Circadian Clock Neurons in Drosophila melanogaster - Reinhard, Nils; Schubert, Frank K.; Bertolini, Enrico; Hagedorn, Nicolas; Manoli, Giulia; Sekiguchi, Manabu; Yoshii, Taishi; Rieger, Dirk; Helfrich-Förster, Charlotte (Frontiers in Physiology, 2022)
Drosophila’s dorsal clock neurons (DNs) consist of four clusters (DN1as, DN1ps, DN2s, and DN3s) that largely differ in size. While the DN1as and the DN2s encompass only two neurons, the DN1ps consist of ~15 neurons, and the DN3s comprise ~40 neurons per brain hemisphere. In comparison to the well-characterized lateral clock neurons (LNs), the neuroanatomy and function of the DNs are still not clear. Over the past decade, numerous studies have addressed their role in the fly's circadian system, leading to several sometimes divergent results. Nonetheless, these studies agreed that the DNs are important to fine-tune activity under light and temperature cycles and play essential roles in linking the output from the LNs to downstream neurons that control sleep and metabolism. Here, we used the Flybow system, specific split-GAL4 lines, trans-Tango, and the recently published fly connectome (called hemibrain) to describe the morphology of the DNs in greater detail, including their synaptic connections to other clock and non-clock neurons. We show that some DN groups are largely heterogenous. While certain DNs are strongly connected with the LNs, others are mainly output neurons that signal to circuits downstream of the clock. Among the latter are mushroom body neurons, central complex neurons, tubercle bulb neurons, neurosecretory cells in the pars intercerebralis, and other still unidentified partners. This heterogeneity of the DNs may explain some of the conflicting results previously found about their functionality. Most importantly, we identify two putative novel communication centers of the clock network: one fiber bundle in the superior lateral protocerebrum running toward the anterior optic tubercle and one fiber hub in the posterior lateral protocerebrum. Both are invaded by several DNs and LNs and might play an instrumental role in the clock network.